None anticipated bacterial urinary tract infections in type 2 diabetic patients relative to duration and angiopathies - Alruba’ae, Salim M. (AL-Kindy College Medical Journal, 2011)
Background: Diabetes mellitus is a well known metabolic and vascular illness associated with high incidence of bacterial urinary tract infections especially in diabetic complications including both micro and macro-vascular types. Objective: To study the incidence of bacterial urinary tract infections in type 2 diabetic patients, the type of micro-organism responsible in relation to age, sex of patients, duration of the disease & related micro & macrovascular diabetic complications. Methods: A prospective study of the diabetic patients including 40 males with mean age of 54(±9) years and 50 females, mean age of 51(±7) years and duration of the and sex matched controls (27 males and 33 females). Symptoms of urinary tract infections, general urine examination, urine culture & ultrasound of abdomen were studied & reported for both groups. Results: This study showed significant increase in urinary tract infections among diabetic patients with four fold rise in bacteriuria especially among diabetic women & Escherechia Coli was the predominant micro-organism in 85% of cases. Conclusion: Urinary tract infection has significant increase incidence in type 2 diabetic patients with fourfold rise among diabetic women.